2020
DOI: 10.7554/elife.54148
|View full text |Cite
|
Sign up to set email alerts
|

Global sleep homeostasis reflects temporally and spatially integrated local cortical neuronal activity

Abstract: Sleep homeostasis manifests as a relative constancy of its daily amount and intensity. Theoretical descriptions define ‘Process S’, a variable with dynamics dependent on global sleep-wake history, and reflected in electroencephalogram (EEG) slow wave activity (SWA, 0.5–4 Hz) during sleep. The notion of sleep as a local, activity-dependent process suggests that activity history must be integrated to determine the dynamics of global Process S. Here, we developed novel mathematical models of Process S bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 93 publications
2
36
0
Order By: Relevance
“…The sleep-wake history of an individual is tracked by physiological processes in the brain in order to homeostatically regulate global vigilance states, such that, for example, sleep deprivation is compensated by increased subsequent sleep duration and intensity. This phenomenon is termed “Process S”, and with an underlying biological substrate that is not completely certain, measures the magnitude of the homeostatic drive to sleep, and can predict with high accuracy EEG slow wave activity through mathematical models (Daan et al, 1984; Achermann et al, 1993; Guillaumin et al, 2018; Thomas et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sleep-wake history of an individual is tracked by physiological processes in the brain in order to homeostatically regulate global vigilance states, such that, for example, sleep deprivation is compensated by increased subsequent sleep duration and intensity. This phenomenon is termed “Process S”, and with an underlying biological substrate that is not completely certain, measures the magnitude of the homeostatic drive to sleep, and can predict with high accuracy EEG slow wave activity through mathematical models (Daan et al, 1984; Achermann et al, 1993; Guillaumin et al, 2018; Thomas et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the finding of a reduced recovery rate of Process S locally in the LFP targeting prefrontal cortex is of potential importance. The global Process S which manifests in slow wave activity at the EEG level has been suggested to result from the integration across the brain of many local Processes S, which in turn each reflect the recent history of local neuronal activities (Thomas et al, 2020). If the rate of Process S recovery is slowed locally in prefrontal regions, it is possible that recovery may occur more quickly elsewhere in the brain, such as more posterior cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active wakefulness associated with higher neuronal activity (Thomas et al , 2020) or EEG theta power (Vassalli and Franken, 2017) has previously been associated with increased homeostatic sleep pressure. The underlying neurobiological substrate of this association remains to be determined, yet its clear implication is that some behaviours may be associated with faster accumulation of sleep need.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that a well-trained task involving the execution of a stereotypical motor-sequence rather than constantly adapting behaviour may be sustained even during localised changes in cortical activity or ‘local sleep’ in some cortical areas. Since evidence suggests that local cortical neuronal activities represent an important factor in governing global sleep homeostasis (Thomas et al , 2020), engagement in well-trained behaviours may therefore result in an attenuated build-up of sleep need during waking. Consistent with this notion, it has been shown that stereotypic, repetitive wheel running is associated with a substantial prolongation of wake periods (Vyazovskiy et al , 2006), yet this does not lead to an increase in cortical excitability, which was previously associated with increased sleep pressure (Huber et al , 2013; Donlea, Pimentel and Miesenböck, 2014; Fisher et al , 2016; Reichert, Pavón Arocas and Rihel, 2019).…”
Section: Introductionmentioning
confidence: 99%